Cessation vs Continuation of Dual Antiplatelet Therapy for Simple Exodontia - Baig, Yumna Shafqat; Hassan, Amna; Muzaffar, Amna; Khan, Ali Akhtar; Sherazi, Ozair; Bhatti, Hassan Tariq (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the outcome among patients of withdrawing antiplatelet therapy compared to continuing their medication prior to simple exodontia in terms of mean bleeding time and frequency of active bleeding.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from May to Nov 2021.Methodology: We included 220 patients of either gender, ranging in age from 40 to 80 years, presenting in the OPD for root simple extraction of mandibular molars, on dual antiplatelet therapy. They were divided into 2 groups on the basis of continuation or discontinuation of medication. Simple extraction was performed, and local hemostatic measures were taken. Post extraction bleeding was monitored and noted for 30 minutes, after which patients were discharged. All participants were asked to contact operating surgeon after 24 hours, in case of any bleeding complication.Results: Out of 220 patients, 127(57.73%) were males and 93(42.27%) were females with male to female ratio of 1.4:1 In this study, mean bleeding time in Group-A, which continued dual oral anticoagulant therapy, was 77.15±4.48 seconds and in Group-B, which discontinued dual oral anticoagulant therapy, was 67.24±7.22 seconds. Bleeding in Group-A, was found in 23 (20.91%) patients and in Group-B, was found in 10 (9.09%) patients (p-value =0.014).Conclusion: Simple exodontia can be caried out in patients continuing oral dual antiplatelet medication by taking local hemostatic measures.